Konseling Individual dalam Mengatasi Perilaku Agresif Siswa - Widia Fauza; Wan Chalidaziah (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2021)
This study aims to determine the implementation of individual counseling to overcome the aggressive behavior of SMA 1 Idi Rayeuk students and to determine the supporting and inhibiting factors for the implementation of individual counseling in overcoming aggressive behavior of SMA 1 Idi Rayeuk students. The aggressive behavior that the author means in this study is the behavior of students who display hostility, feelings of anger, acts of hurting both physically and non-physically, this is where guidance and counseling services need to be applied. This research is a case study research (case study), the approach used in this research is qualitative. Sources of research data, namely counseling guidance teachers at SMA 1 Negeri Idi Rayeuk 2 people, and 7 students, data collection techniques by means of observation interviews and documentation. The results of this study indicate that the implementation of individual counseling on aggressive students using individual counseling, individual counseling overcoming serious student problems. Meanwhile, for mild student problems, it is enough only to be reprimanded and advised by the homeroom teacher and counseling teacher. The stages of individual counseling for students who engage in aggressive behavior are carried out in three stages, the opening stage, the core activity stage and the closing stage, the results obtained for the implementation of individual counseling on students at SMA Negeri 1 Idi Rayeuk are fruitful, students begin to be able to face all problems patiently and a cool head. Students have the ability to make choices or actions for their survival. Students have also started to gradually change their behavior, students have also started to open themselves up to communicate with their closest people such as their parents, siblings, and friends.